2016
DOI: 10.1097/brs.0000000000001812
|View full text |Cite
|
Sign up to set email alerts
|

Management of Locally Recurrent Chordoma of the Mobile Spine and Sacrum

Abstract: Study Design Systematic review. Objective To determine evidence-based guidelines for the management of locally recurrent spinal chordoma. Summary of Background Data Chordoma of the spine is a low-grade malignant tumor with a strong propensity for local recurrence. Salvage therapy is challenging due to its relentless nature and refractoriness to adjuvant therapies. There are currently no guidelines regarding the best management of recurrent chordoma. Methods We combined the results of a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Most of the reports related to chordoma evaluated primary chordomas and recurrent chordomas en bloc, but we focused on residual or recurrent chordomas. 21,29,30 Ailon et al 6 suggested that further complete surgical resection can be considered for local recurrent chordoma, even if the management of recurrent chordoma is challenging and may be palliative. We supposed that follow-up MR imaging using ADC mapping could discriminate small chordomas with an aggressive potential from those without it; this discrimination could allow a short follow-up or early salvage therapy (further surgical resection) that would likely be successful or effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the reports related to chordoma evaluated primary chordomas and recurrent chordomas en bloc, but we focused on residual or recurrent chordomas. 21,29,30 Ailon et al 6 suggested that further complete surgical resection can be considered for local recurrent chordoma, even if the management of recurrent chordoma is challenging and may be palliative. We supposed that follow-up MR imaging using ADC mapping could discriminate small chordomas with an aggressive potential from those without it; this discrimination could allow a short follow-up or early salvage therapy (further surgical resection) that would likely be successful or effective.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize recurrence early to ensure adequate salvage therapy. 6,13 Although radiologic evaluation is important in oncology, assessment of tumor progression or response to treatment is based on changes in the residual tumor size on imaging. 14 ADC can identify further characteristics of many tumors with malignant potential.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, whether postoperative radiotherapy was beneficial for patients with an intraspinal tumor that was incompletely resected was still controversial (2,17). Tumor resection method (tumor margin) was a universally acknowledged prognostic factor for almost all resectable malignant tumors (1,4,13). In our study, most of the benign-appearing intraspinal MPNSTs were intradural extramedullary tumors (accounting for 78.6%).…”
mentioning
confidence: 73%
“…Owing to its rarity, limited information regarding to clinical experience and prognostic analysis of spinal chordoma has been reported, but most of published information only focused on prognosis of primary spinal chordoma, with less attention on recurrent cases especially repeatedly recurrent cases. Tamir Ailon et al [10] systematically reviewed main published articles about recurrent spinal chordoma and obtained guidance in regard to the management of recurrent cases. Wide en bloc resection should be achieved if technically feasible with appropriate cases, and high-dose radiation therapy was suggested to administer postoperatively to reduce the risk of local recurrence.…”
Section: Introductionmentioning
confidence: 99%